Magnitude and determinants of occupational exposure to blood and body fluids among physicians in a teaching hospital in northern Ethiopia - Hayelom Weldetekle; Hale Teka; Hagos Gidey; Assefa Sharew; Mebrihit Gebremeskel; Ruta Mehari Tafere; Hailesllassie Berhe (Scientific Reports)
Abstract Occupational exposure to blood and body fluids (BBF) poses a significant risk for transmission of blood-borne pathogens among healthcare workers, especially in low-income countries. Physicians are at higher risk due to their direct involvement in patient care. The aim of this study was to investigate the prevalence and factors associated with occupational exposure to blood and body fluid exposure among physicians in a teaching hospital in northern Ethiopia. An institutional cross-sectional study was conducted at Ayder Comprehensive Specialized Hospital from January 1–March 31, 2020. A total of 255 physicians were selected by simple randomization. Data were collected using a structured self-reported questionnaire. Descriptive statistics were used to summarize the data. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with blood and body fluid exposure. Of the 255 participants, 188 (73.7%) were male, and the mean age was 28.21 years (SD ± 4.08). The prevalence of occupational exposure to blood and body fluid in the last three months was 94 (36.9%), and lifetime exposure was 210 (82.4%). Exposure was most common among residents (52.1%) and interns (35.1%). The highest exposure rates occurred in the departments of obstetrics and gynecology (30.8%) and general surgery (24.5%). Working more than 8 h per day (AOR = 4.87, 95% CI 2.46–9.63), lack of infection prevention training (AOR = 5.36, 95% CI 1.83–15.72) and inconsistent use of gloves (AOR = 3.08, 95% CI 1.69–5.61) were significantly associated with BBF exposure. Occupational exposure to blood and body fluid exposure is high among physicians, especially among residents and interns. Factors such as long working hours, lack of infection prevention training and inconsistent use of personal protective equipment contribute to this risk. Measures to provide training, ensure the availability and consistent use of personal protective equipment and manage workload are essential to reduce occupational exposure.